2012
DOI: 10.1371/journal.pone.0042863
|View full text |Cite
|
Sign up to set email alerts
|

The Proteolytic Activity of Separase in BCR-ABL-Positive Cells Is Increased by Imatinib

Abstract: Separase, an endopeptidase required for the separation of sister-chromatides in mitotic anaphase, triggers centriole disengagement during centrosome duplication. In cancer, separase is frequently overexpressed, pointing to a functional role as an aneuploidy promoter associated with centrosomal amplification and genomic instability. Recently, we have shown that centrosomal amplification and subsequent chromosomal aberrations are a hallmark of chronic myeloid leukemia (CML), increasing from chronic phase (CP) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…In addition to its multi-targeted mechanism of action (see Introduction), imatinib (as well as nilotinib and dasatinib) was documented to induce spindle defects, numerical and structural centrosome and chromosome alterations in human and mammalian cells in vitro in a dose-dependent manner. Also, these inhibitors affected centrosomes and spindles and induced de novo chromosomal aberrations in CML cells as well as in BCR-ABL-negative hematopoietic progenitor cells in vivo (Cohen et al, 2002;Fabarius et al, 2008Fabarius et al, , 2007Fabarius et al, , 2005Giehl et al, 2010;Haaß et al, 2012). Aditionally, the most widely used plant-based bioassays for the detection of genotoxins demonstrated that imatinib at low concentrations caused induction of micronucleuses, which are formed as a consequence of numerical and structural chromosomal damage (Pichler et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its multi-targeted mechanism of action (see Introduction), imatinib (as well as nilotinib and dasatinib) was documented to induce spindle defects, numerical and structural centrosome and chromosome alterations in human and mammalian cells in vitro in a dose-dependent manner. Also, these inhibitors affected centrosomes and spindles and induced de novo chromosomal aberrations in CML cells as well as in BCR-ABL-negative hematopoietic progenitor cells in vivo (Cohen et al, 2002;Fabarius et al, 2008Fabarius et al, , 2007Fabarius et al, , 2005Giehl et al, 2010;Haaß et al, 2012). Aditionally, the most widely used plant-based bioassays for the detection of genotoxins demonstrated that imatinib at low concentrations caused induction of micronucleuses, which are formed as a consequence of numerical and structural chromosomal damage (Pichler et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, separase, a cysteine endopeptidase involved in triggering anaphase and the maintenance of centriole numbers through cohesion hydrolysis, was highly expressed in CML cells (Haaß et al, 2012;Patel and Gordon, 2009).Two putative separase cleavage sites were identified in the CrkL sequence at amino acid positions 67-70 and 139-142 by sequencing analysis. It is therefore possible that Pickles could be cleaved by this protease, which might explain the disappearance of small bands that should be observed after cleavage at D94 by metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%
“…Third, full-length proteins are cleaved and degraded. Because it was reported that the expression of BCR-ABL induces protease expression (Haaß et al, 2012;Patel and Gordon, 2009) and promotes proteasome activity (Crawford et al, 2009;Magill et al, 2004), we tested the possibility of the third scenario. To evaluate this possibility, we introduced a silent mutation into the EcoRI site in CrkL (Pickles 2.33, see also Fig.…”
Section: Pickles Is Cleaved At Multiple Positionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we have skipped use of the Cy5 label and have used this detection channel for simultaneous sorting of CD34 + cells. In our earlier work [36], we have used a lysate-based separase assay that worked with a comparable reporter peptide, but measured separase activity in protein lysates [27]. Back then, we have indeed used actin (immunostained Western blots) to normalize for separase activity.…”
Section: Measurement Of Separase Proteolytic Activity and Cell Sortinmentioning
confidence: 99%